Ḥabl aṣ-Ṣaḫr 1983-1985: Nebuchadnezzar II's Cross-country Wall North of Sippar - Black, J.A. (1987)
esp. p. 15-21: Babylonian Textual Evidence by J.A. Black; p.29-35: Stamped Bricks Recovered from ?abl a?-?a?r by J.A. Black; = NAPR 1